SIKAP ETIS HAMBA TUHAN DALAM BERDOA MELALUI MEDIA SOSIAL - Daeli, Miseri Cordia Domini (Jurnal Matetes STT Ebenhaezer, 2022)
Abstract The purpose of this paper is for God's servants to maintain ethics in praying through social media, because in the 4.0 era, there were many people who were affected by it so it was very difficult to control themselves from technological advances and one of them was through social media. Most people today submit their complaints through social media to God, they don't know that it's not good to be conveyed on social media, because if it's through social media, automatically many people will know about it. And in this writing, talk about how the ethical attitude of God's servants in praying through social media. Of course, God's servants are required to do something ethically, so in this case God's servants must know what the actual ethics are in terms of praying through social media, meaning we have to pay attention to our prayers that we convey, whether it has motivation so that everyone knows it and praises him or not, it depends on each of us personally, so that when we don't have this kind of motivation, the author believes that we as God's servants do not convey our complaints to God through social media because such things are unethical. When praying to God either through social media, even within the family or even personally, we have to be serious, because what God knows is that our hearts are not where we are praying. because one way to build a relationship with God is one of them praying, so praying to God is very necessary. Abstrak Tujuan dari penulisan ini ialah supaya hamba-hamba Tuhan tetap menjaga etika dalam berdoa melalui media sosial, sebab pada masa era 4.0, ada banya orang yang terpengaruh didalamnya sehingga sangat sulit untuk mengendalikan diri dari kemajuan teknologinya dan salah satunya ialah melalui media sosia. Kebanyakan orang pada masa kini menyampaikan keluhannya melalui media sosial kepada Tuhan mereka tidak tahu bahwa itu tidak baik untuk disampaikan dimedia sosial, karena jikalau melalui media sosial maka otomatis banyak orang yang mengetahuinya. Dan dalam penulisan ini, berbicara tentang bagaimana sikap etis hamba Tuhan dalam berdoa melalui media sosial. Tentu hamba-hamba Tuhan dituntut untuk melakukan sesuatu hal itu dengan beretika, sehingga dalam hal ini hamba-hamba Tuhan harus tahu bagaimana etika yang sebenarnya dalam hal berdoa melalui media sosial, artinya kita harus memperhatikan doa kita yang kita sampaikan itu, apakah hal itu memiliki motifasi supaya semua orang mengetahuinya dan memuji dia atau tidak, itu tegantung pribadi lepas pribadi kita masing-masing, sehingga ketika kita tidak memiliki motifasi seperti ini maka penulis percaya kita sebagai hamba-hamba Tuhan tidak menyampaikan keluhan-keluhan kita kepada Tuhan melalui media sosial karena hal-hal seperti itu kurang beretika. Ketika Berdoa kepada Tuhan baik melalui media sosial bahkan dalam keluarga bahkan secara pribadi pun kita harus sungguh-sungguh, sebab yang diketahui Tuhan ialah hati kita masing-masing bukan keberadaan kita dimana kita berdoa. karena salah satu cara untuk membangun relasi kepada Tuhan ialah salah satunya berdoa, jadi berdoa kepada Tuhan sangat perlu.